Uncovering Global SUMOylation Signaling Networks in a Site-Specific Manner - Hendriks, Ivo A. (Nat Struct Mol Biol, 2014)
SUMOylation is a reversible post-translational modification essential for genome stability. Using high-resolution mass spectrometry, we have studied global SUMOylation in human cells and in a site-specific manner, identifying a total of over 4,300 SUMOylation sites in over 1,600 proteins. Moreover, for the first time in excess of 1,000 SUMOylation sites were identified under standard growth conditions. SUMOylation dynamics were quantitatively studied in response to SUMO protease inhibition, proteasome inhibition and heat shock. A considerable amount of SUMOylated lysines have previously been reported to be ubiquitylated, acetylated or methylated, indicating crosstalk between SUMO and other post-translational modifications. We identified 70 phosphorylation and 4 acetylation events in close proximity to SUMOylation sites, and provide evidence for acetylation-dependent SUMOylation of endogenous histone H3. SUMOylation regulates target proteins involved in all nuclear processes including transcription, DNA repair, chromatin remodeling, pre-mRNA splicing and ribosome assembly.